Reduced Glutathione Level Promotes Epithelial-Mesenchymal Transition in Lens Epithelial Cells via a Wnt/β-Catenin–Mediated Pathway: Relevance for Cataract Therapy - Wei, Zongbo (Am J Pathol, 2017)
The epithelial-mesenchymal transition (EMT) process plays a pivotal role in the pathogenesis of posterior capsular opacification because of remnant lens epithelial cell proliferation, migration, and transformation after cataract surgery. The latter, we hypothesize, may result in posterior capsule wrinkling and opacification because of a profound change in the lens growth environment via a 1000-fold reduction of extracellular glutathione (GSH) levels. To test this hypothesis, we investigated the EMT process in cell culture and GSH biosynthesis deficiency mouse models. Our data indicate a dramatic increase of pro-EMT markers, such as type I collagen, α-smooth muscle actin, vimentin, and fibronectin, under conditions of lens GSH depletion. Further study suggests that decreased GSH triggers the Wnt/β-catenin signal transduction pathway, independent of transforming growth factor-β. Equally important, the antioxidants N-acetyl cysteine and GSH ethyl ester could significantly attenuate the EMT signaling stimulated by decreased GSH levels. These findings were further confirmed by mock cataract surgery in both gamma glutamyl-cysteine ligase, catalytic subunit, and gamma glutamyl-cysteine ligase, modifier subunit, knockout mouse models. Remarkably, increased EMT marker expression, β-catenin activation, and translocation into the nucleus were found in both knockout mice compared with the wild type, and such increased expression could be significantly attenuated by N-acetyl cysteine or GSH ethyl ester treatment. This study, for the first time we believe, links oxidative stress to lens fibrosis and posterior capsular opacification formation via EMT-mediated mechanisms.